PENGARUH KINERJA LINGKUNGAN, FOREIGN OWNERSHIP PADA KINERJA KEUANGAN DENGAN PENGUNGKAPAN CSR SEBAGAI VARIABEL INTERVENING - Pramudya, Alvyn Syahru; Musyarofah, Siti (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2023)
This study purpose to determine the effect of environmental performance, foreign ownership on financial performance with Corporate Social Responsibility disclosure as an intervening variable. The total population of energy and manufacturing companies listed on the Indonesian Stock Exchange (IDX) for 2018-2021 is 335 companies. The samples analyse 63 samples based on the purposive random sampling method. This study uses secondary data, namely financial reports, suistainability reports and sustainability reports for 2018-2021 obtained from the Indonesian Stock Exchange website and company sites. Data analysis used the Partial Least Square-PLS method. The results show that environmental performance has no effect on financial performance, environmental performance has no effect on CSR disclosure, foreign ownership has an effect on financial performance, foreign ownership has no effect on CSR disclosure, CSR disclosure has no effect on financial performance, and CSR variable cannot be a variable intervene.